Targeted proteins involved in the neuroprotective effects of lithium citrate - I. Yu. Torshin; O. A. Gromova; L. A. Mayorova; A. Yu. Volkov (Неврология, нейропсихиатрия, психосоматика, 2017)
Preparations based on organic lithium salts are promising neuroprotective agents that are effective just in the micromolar concentration range and, at the same time, have high safety (Toxicity Class V).Objective: to elucidate more detailed mechanisms responsible for the biological and pharmacological effects of lithium citrate, by analyzing the possible interactions of lithium ion with human proteome proteins that are also represented in the rat proteome.Material and methods. The targets of lithium are two proteins, such as glycogen synthase-3β (GSK-3β) and inositol monophosphatase 1 (IMPA1), were experimentally validated using lithium citrate.Results. The cycle use of oral lithium citrate was shown to decrease the activity of these proteins in the rat brain hydrolysates. The effects of lithium were analyzed in the human and rat proteomes. 47 proteins were ascertained to be present in the human and rat proteomes, the activity of which depended on lithium ions. There were 4 groups of lithium-dependent proteins: 1) the proteins regulated by GSK3β kinase; 2) those modulating the level of inositol phosphates; 3) those modulating the metabolism of neurotransmitters; 4) those working via other mechanisms.